The Historical Evolution of Christianity in Pakistan: Missionary Influence, Caste Dynamics, and the Challenge of Theological Contextualization - Ali, Farman; Khan, Hafiz Waqas; Riaz, Shehla; Haq, Ikram ul; Ahmed, Kamran (Journal of Islamic Thought and Civilization, 2025)
This study explores the historical development, socio-economic struggles, and identity challenges of Pakistani Christians from the pre-colonial period to the present day. It examines the role of missionary expansion, particularly the chūhrā mass movement (1868–1931), which shaped the demographic and social structure of the Christian community. The study highlights the impact of caste-based discrimination, economic marginalization, and denominational fragmentation, which have reinforced internal divisions and hindered social mobility. Following Partition, issues such as land dispossession and limited employment opportunities further entrenched Christians in sanitation work, reinforcing societal stereotypes. Additionally, the study addresses the complexity of Christian identity, which is shaped by religion, ethnicity, and nationality, yet remains unresolved due to social exclusion and Western influences. The research underscores the need for theological contextualization, social integration, and economic empowerment to foster a more unified and resilient Christian community in Pakistan.